Experimental Of Tailor Welded Blanks Fabricated Using Friction Stir Welding (FSW) - Pauzi, Adha Fahmi (Universiti Sains Malaysia, 2018)
Friction stir welding (FSW) is a relatively new joining process and has produced a big impact on several industries due to many advantages over traditional welding process. The present works aims investigate the feasibility of welding two pieces of aluminum alloy (AA 6061) sheets of thickness 3mm by FSW process. This main objective of this research is to study the effect on tensile strength, hardness and roughness with respect to feed rate (welding speed), spindle speed (rotation speed), and tool angle and to optimize the FSW parameters. Three level of feed rate i.e. at 31, 65, and 90 (mm/min), spindle speed at 600, 865, and 1140 (rpm) and tool angle at 2, 3, 4 (°) were used in the experiment. The fixture clamp fixed on the conventional milling machine has been design and fabricate to enable this welding. FSW tools were designed and fabricated from tool steel. In this study, tensile strength, hardness and roughness of FSW is optimized using Taguchi L9 orthogonal design of experiments. The tensile and hardness test were conducted to determine the mechanical properties of the weld and roughness test were carried out to determine the surface roughness of the weld. The hardness pattern was found to the lowest at the centre of the weld zone. The tool shoulder depth plays the role on surface roughness. The optimum process parameters were determined with reference to DoE performed. The spindle speed and feed rate are the most significant parameters to the tensile strength of the weld.